Acca sellowiana (Myrtaceae): A New Alternative Host for Drosophila suzukii (Diptera: Drosophilidae) in Brazil - Souza G.K.* (2017)
We report, for the first time, the occurrence and development of Drosophila suzukii Matsumura (Diptera: Drosophilidae) in fruits of Acca sellowiana (Berg) Burret (Myrtaceae). Although fruits of A. sellowiana present hard and thick skin, damage caused by another insect pest, Conotrachelus psidii Marshall (Coleoptera: Curculionidae), may have enabled fruit infestation by D. suzukii.